Implementasi Kurikulum Muatan Lokal Pada Pembelajaran Aksara Arab Melayu Melalui Strategi Aransemen Lagu di SD Al-Azhar Medan Sumatera Utara - Mursal Aziz; Putri Azkia; Zulfa Zakiyyah; Rahmanita Minta Ito Pulungan (LPPM Politeknik Pratama, 2024)
This research aims to find out about the strategies used by teachers in delivering Malay Arabic script learning material to students through arranging a song at SD Al-Azhar Medan. The method used in this research is qualitative. Nowadays, song composing activities are not only carried out for entertainment purposes alone, and are not only carried out by singers for their own needs, but now song arrangements are used by teachers, as a medium that can support learning. This is done because today's children prefer to listen to something that sounds like a song rather than listening to the teacher explain, therefore today's teachers change song lyrics into learning material so that they are easy for students to remember. The research findings are that song arrangements in Malay Arabic script learning activities are a very unique learning strategy and are also effectively used in Malay Arabic script learning so that students will be more enthusiastic and will also understand the learning more easily and through arranging a song learning activities will also have an impact. positive impact on student learning outcomes.